A Job Satisfaction Among The Employees At Redang Mutiara Resort - Norazmi Omar (2006)

(untitled)
This is a study of job satisfaction among the employees at Redang Mutiara Resort. A study of job satisfaction is important because it has direct implications for organization functioning. Apart of examining the job satisfaction among the employees, the aim of the study was also to identify the overall management system that was being practiced in the resort. In addition, the study also tried to determine the relationship between management style and job satisfaction. The study employed a modified Likert scale to measure organizational management profile and the Job Diagnostic Survey developed by Hackman and Oldham to measure job satisfaction. A questionnaire was developed to obtain data from the populations in the resort. Data analysis was done using the SPSS programme. Statistical analysis was done using the Spearman's rank-order correlation for the ordinal data and the chi-square test for the nominal data. The overall job satisfaction level among the employees in the resort was found to be 'slightly satisfied'. It was also found that job satisfaction was related to management style and slightly influenced by personnel characteristics such as gender and age. Several recommendations have been put forward in order to improve the job satisfaction in the resort. (Author's abstract)